Small Diatribes from the Cenacle. Mario Benedetti's First Theater as a (Failed?) Three-Dimensional Essay (Revista de Crítica Literaria Latinoamericana, 2013)
In Mario Benedetti’s career, playwriting was sporadic and often undervalued, even by the author himself. However, his "pieces for writers", a theatrical trilogy composed between the 1950s and the 60s, are built as essays and journeys around the literary debates that shaped Uruguayan culture of the time, acquiring for that reason a remarkable historical value. In these works Benedetti defines the national "literary" object and its possible ethics (Ustedes, por ejemplo ); transforms the space of the theatre into meta-theatre with its consequential parody of the stage system (Ida y vueltã)' and describes different narrative possibilities (El reportaje). This paper analyzes these works as a unified project: Benedetďs attempt to insert his writings into the procedures and reflections on literature and creation, thereby instituting an "object that analyzes and simultaneously is analyzed" (Roland Barthes) and, by extension, generating a new theatricality and a new scenic language.
Keywords: metatheater; essay scene; theatrical system; debate